Foster care as a form of substitute care in the black community : an exploratory-descriptive study - Sishuta, Happy Babalwa (Rhodes University, Faculty of Humanities, Department of Social Work, 1996)
Kinship care is increasingly supplementing the more traditional forms of out-of-home care. Because related foster care has potential great value, the possibility of placement with relatives needs to be explored first. At its best it provides the child love and security with known people and possibly in a familiar environment. Yet, important as it is, this area of practice is seriously underdeveloped - few publications especially in South Africa exist on how children fare in this arrangement. This situation exists in spite of the fact that many children find themselves in both legal as well as privately arranged related foster care placements. Equally of course no comprehensive study has been undertaken to study the black family's perception of formal foster care and their adjustment to formal foster care practice which for many is a new encounter in their lives. More clarity on these issues pertaining to kinship care will not only improve our understanding but can lead to a better service. Socio-political influences have weakened the mutual aid system in African families. This has resulted in needsÂ· and problems which the African family find it difficult to deal with. This has prompted families to make use of non-family support particularly services from specialized and other welfare agencies. Formal foster care is a foreign practice to the black community as a result of their tradition and custom. It offers a new method of coping with child care problems and indicates a shift from the conventional patterns among South African blacks. As a result there is often confusion and a lack of understanding, making the community not to make proper use of this service. This study is exploratory-descriptive. The sample comprised thirty foster parents. The main objective of this study was to investigate the nature and practice of formal foster care in the black community with specific emphasis on related foster care and its perception. The study has raised a number of issues for practice and policy consideration. Notable findings were: the need to (1) promote much more active involvement of foster parents, foster child and their families (2) educate the community about foster care (3) prepare, train, support and supervise foster parents. The study revealed that these placements have become indistinguishable from natural parenthood and the foster children have become absorbed into the foster family. A need exists for permanency planning in foster care. It is hoped that the research findings will contribute to the existing body of knowledge and that more studies will be undertaken in future.
Keywords: Foster home care -- South Africa; Kinship care -- South Africa; Children, Black -- Services for -- South Africa; Black people -- Services for -- South Africa